The Role and Place of American Journal of Criminal Justice in the Discipline - Miller, Alexis J. (American journal of criminal justice, 2012)
The American Journal of Criminal Justice (AJCJ), the peer-reviewed publication of the Southern Association of Criminal Justice (SCJA), has been in publication for 35 years. SCJA has often been viewed as an approachable association to become involved with for young faculty in criminal justice. In addition, based on the findings of this assessment, SCJA’s journal has also been viewed as a desirable starting place for new academics to foray into the world of peer-reviewed publications. This article reviews the 35 year history of AJCJ’s articles and authors by addressing the trends in subjects, methods, authors, and citations to articles in the journal.